Case Report: Extended Clinical Spectrum of the Neonatal Diabetes With Congenital Hypothyroidism Syndrome - Splittstoesser, Vera; Vollbach, Heike; Plamper, Michaela; Garbe, Werner; De Franco, Elisa; Houghton, Jayne A. L.; Dueker, Gesche; Ganschow, Rainer; Gohlke, Bettina; Schreiner, Felix (Frontiers in Endocrinology, 2021)
Background: Neonatal diabetes with congenital hypothyroidism (NDH) syndrome is a rare condition caused by homozygous or compound heterozygous mutations in the GLI-similar 3 coding gene GLIS3. Almost 20 patients have been reported to date, with significant phenotypic variability. Case presentation: We describe a boy with a homozygous deletion (exons 5-9) in the GLIS3 gene, who presents novel clinical aspects not reported previously. In addition to neonatal diabetes, congenital hypothyroidism and other known multi-organ manifestations such as cholestasis and renal cysts, he suffered from hyporegenerative anemia during the first four months of life and presents megalocornea in the absence of elevated intraocular pressure. Compensation of partial exocrine pancreatic insufficiency and deficiencies in antioxidative vitamins seemed to have exerted marked beneficial impact on several disease symptoms including cholestasis and TSH resistance, although a causal relation is difficult to prove. Considering reports on persistent fetal hemoglobin detected in a few children with GLIS3 mutations, the transient anemia seen in our patient may represent a further symptom associated with either the GLIS3 defect itself or, secondarily, micronutrient deficiency related to exocrine pancreatic deficiency or cholestasis. Conclusions: Our report expands the phenotypic spectrum of patients with GLIS3 mutations and adds important information on the clinical course, highlighting the possible beneficial effects of pancreatic enzyme and antioxidative vitamin substitutions on characteristic NDH syndrome manifestations such as TSH resistance and cholestasis. We recommend to carefully screen infants with GLIS3 mutations for subtle biochemical signs of partial exocrine pancreatic deficiency or to discuss exploratory administration of pancreatic enzymes and antioxidative vitamins, even in case of good weight gain and fecal elastase concentrations in the low-to-normal range.